Neuroprotective Effects of Treadmill Exercise in Hippocampus of Ovariectomized and Diabetic Rats. (1st August 2022) - Zare, Zohreh; Zarbakhsh, Sam; Tehrani, Mohsen; Mohammadi, Moslem
Highlights: Treadmill exercise attenuated apoptosis-induced neuropathology in ovariectomized rat hippocampus. Treadmill exercise inhibited apoptosis and improved neuronal survival in diabetic rat hippocampus. Treadmill exercise significantly recovered acetylcholinesterase activity in diabetic rat hippocampus. Treadmill exercise had no neuroprotective effects in ovariectomized diabetic rat hippocampus. Abstract: To determine detrimental effects of estrogen and insulin deficiencies on hippocampus, we examined apoptosis-induced neuronal damage and cholinergic system in ovariectomized and/or diabetic rat hippocampus. Possible neuroprotective effects of treadmill exercise were also investigated. Adult female Wistar rats were randomly divided into four groups ( n = 5 rats/group) as follows: control, ovariectomized (Ovx), diabetic (Dia, streptozotocin (STZ) 60 mg/kg; i.p.), and Ovx + Dia groups. Each group was further subdivided into exercise and non-exercise groups. Animals in exercise groups were subjected to treadmill training, while those in non-exercise groups were placed on the stationary treadmill for 4 weeks (5 days/week). Apoptosis-related protein levels (i.e. Bax, Bcl-2, and caspase-3), number of survived neurons, and acetylcholinesterase (AChE) activity in the hippocampus were measured using Western blotting, Cresyl Violet staining, and Ellman assay, respectively. Both ovariectomy and diabetes increased expression of Bax and caspase-3 and decreased expression of Bcl-2 at protein levels. In addition, a significant decrease in the number of survived neurons was observed in both Ovx and Dia groups, while AChE activity was lower only in the Dia group. The Ovx + Dia group showed stronger apoptosis-induced neuropathology and inhibition of AChE activity. Treadmill exercise attenuated apoptosis-induced neuropathology in the Ovx and Dia groups and recovered AChE activity in the Dia group. Neuroprotective effects of treadmill exercise were mediated by inhibition of apoptosis. Moderate exercise protocol had no beneficial anti-apoptotic and neuroprotective effects in ovariectomized-diabetic rats.